STRATEGI GAME-BASED LEARNING UNTUK MENUMBUHKAN KEBIASAAN POSITIF MENGELOLA DIRI DAN SUMBER DAYA - Jakaria, Pri; Dewi Apriani; Beni habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effectiveness of implementing game-based learning strategies to promote positive habits in managing oneself and available resources. The issue addressed is the lack of student engagement and limited contextual understanding when character-related concepts are delivered through traditional instruction. The main objective of the study is to design and evaluate a learning approach that encourages active participation and internalization of values such as discipline, responsibility, and initiative. Employing a qualitative descriptive method, the research involved observation, interviews, and structured questionnaires to collect data from selected student groups within a formal education setting. The instructional model incorporated educational games that simulate real-life scenarios requiring decision-making, time management, and teamwork. Thematic analysis was conducted to interpret the collected data, highlighting key behavioral changes and learning outcomes. The findings reveal that students responded positively to the interactive format, showing increased motivation, collaboration, and consistency in applying self-regulation strategies. Additionally, the integration of game elements supported differentiated learning while embedding value-oriented messages in a meaningful and engaging manner. This study suggests that game-based learning has the potential to serve as an effective pedagogical tool to enhance character development in primary education.